Extracellular polymeric substance architecture influences natural genetic transformation of acinetobacter baylyi in biofilms - Merod, Robin T. (2015)
Genetic exchange by natural transformation is an important mechanism of horizontal gene transfer in biofilms. Thirty-two biofilm metrics were quantified in a heavily encapsulated Acinetobacter baylyi strain and a miniencapsulated mutant strain, accounting for cellular architecture, extracellular polymeric substances (EPS) architecture, and their combined biofilm architecture. In general, transformation location, abundance, and frequency were more closely correlated to EPS architecture than to cellular or combined architecture. Transformation frequency and transformant location had the greatest correlation with the EPS metric surface area-to-biovolume ratio. Transformation frequency peaked when EPS surface area-to-biovolume ratio was greater than 3 μm2/μm3 and less than 5 μm2/μm3. Transformant location shifted toward the biofilm-bulk fluid interface as the EPS surface area-to-biovolume ratio increased. Transformant biovolume was most closely correlated with EPS biovolume and peaked when transformation occurred in close proximity to the substratum. This study demonstrates that biofilm architecture influences A. baylyi transformation frequency and transformant location and abundance. The major role of EPS may be to facilitate the binding and stabilization of plasmid DNA for cellular uptake.